The Influence of Brand Image and Price on Purchasing Decisions at the Ampera Restaurant in Bandung - Dewi Indriani Jusuf (SEAN Institute, 2024)
Rumah Makan Ampera Bandung, known for its traditional food and Sundanese dining experience, has become a top destination for local and international tourists. In order to increase understanding of the factors that influence consumer purchasing decisions, this research aims to analyze the influence of brand image and price on purchasing decisions at Rumah Makan Ampera Bandung. This research method uses a quantitative approach with data collection techniques through questionnaires to a sample of consumers who visit the Ampera Restaurant in Bandung. The collected data was analyzed using the regression method to test the relationship between brand image, price and purchasing decisions. Based on partial correlation analysis, brand image and price have a positive and significant effect on purchasing decisions at the Ampera Bandung restaurant. Based on simultaneous analysis of brand image and price, it has a positive and significant effect on purchasing decisions at Ampera Bandung restaurants.